Metabolic Equivalent Determination in the Cultural Dance of Hula - Usagawa, T.; Look, M.; de Silva, M.; Stickley, C.; Kaholokula, J. K.; Seto, T.; Mau, M. (International Journal of Sports Medicine, 2014)
Ethnic minorities share an unequal burden of cardiometabolic syndrome. Physical activity (PA) has been shown to be an important factor for improving the outcomes of these diseases. While metabolic equivalents (METs) have been calculated for diverse activities, most cultural activities have not been evaluated. Hula, the traditional dance of Native Hawaiians, is practiced by men and women of all ages but its MET value is unknown. To our knowledge, this is the first scientific evaluation of energy expenditure of hula. 19 competitive hula dancers performed 2 dance sets of low- and high-intensity hula. METs were measured with a portable indirect calorimetry device. Mean and standard deviations were calculated for all the variables. A 2-way ANOVA was conducted to identify differences for gender and intensity. The mean MET were 5.7 (range 3.17–9.77) and 7.55 (range 4.43–12.0) for low-intensity and high-intensity, respectively. There was a significant difference between intensities and no significant difference between genders. This study demonstrates that the energy expenditure of both low- and high-intensity hula met the recommended guidelines for moderate and vigorous intensity exercise, respectively, and that hula can be utilized as a prescribed PA.
Keywords: native hawaiian; cultural competency; energy expenditure; exercise